Story of Islam the flowering of Islam [videorecording] - Dooley, John. ([S.l.] Polonius Production, 1991)
Summary: An overview of Islam chronicling the religion's historical impact unto the modern world, and discussing its origins, basic beliefs and structure.
Keywords: Islam -- History; Arabs and Islam; Civilization, Islamic; Islamic countries -- Civilization